2009
DOI: 10.5851/kosfa.2009.29.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Supplementation on Beef Color Stability

Abstract: The objective of this study was to investigate the supplementation effect of selenium on beef color stability. A total of 15 Hanwoo steers were divided into 3 groups and 2 groups were administered with 0.9 ppm of one of two organic-selenium products, Organic-Se and Se-SMC (Se-spent mushroom compost) for 4 mon. The third group was the control group, which was not with fed selenium during the same period. The result of this study showed that there was no significant difference in meat color between the control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…On the contrary, literature shows that organic selenium supplementation to Hanwoo steers did not affect the beef colors [26]. Another study also reported that the source of selenium did not significantly affect cook loss and sensory quality of the cooked pork (p > 0.05) [27].…”
Section: Effect Of Different Selenium Levels On Physicochemical Quality Of Beef Muscles and Organsmentioning
confidence: 99%
“…On the contrary, literature shows that organic selenium supplementation to Hanwoo steers did not affect the beef colors [26]. Another study also reported that the source of selenium did not significantly affect cook loss and sensory quality of the cooked pork (p > 0.05) [27].…”
Section: Effect Of Different Selenium Levels On Physicochemical Quality Of Beef Muscles and Organsmentioning
confidence: 99%